Prevocational exposure to public health in the Kimberley: A pathway to rural, remote and public health practice. (April 2014) - Hofer, Alexandra; Parker, Jake; Atkinson, David; Moore, Sarah; Reeve, Carole; Mak, Donna B.
Abstract Objective To evaluate the Kimberley Population Health Unit (KPHU) prevocational public health placement in terms of its contribution to resident medical officers' (RMOs') knowledge, skills, career path and aspirations. Design All RMOs who had completed a public health placement at the KPHU (n = 27) during 2001–2012 were invited to complete an online survey in September 2012. Setting The KPHU, based in Broome, provides population health services to the Kimberley region, far north Western Australia. Main outcome measures The extent to which RMOs perceived the development of public health skills and knowledge during the placement, and the degree to which RMOs believe this placement influenced future career pathways and their current practice. Results Twenty‐three RMOs (85%) completed the survey. Sixty per cent are currently working in general practice or public health medicine; of these, 43% have returned to the Kimberley. Over 70% reported that the placement developed their knowledge of public health and Aboriginal health to a 'great' or 'very great' extent. Sixty‐one per cent felt that their placement influenced their future desire to work in public health 'a lot' or 'a great extent'. Conclusion This placement provides a unique opportunity for RMOs to undertake public health and Aboriginal health work in a remote setting. Given the increasing demand for prevocational placements, the value of imparting sound public health knowledge to the next generation of doctors and the urgent need to recruit and retain rural doctors, this placement provides a potential model that could be expanded to other locations.